Sodium lasalocid and concentrate/roughage ratio effects on productive performance of lactating cows - Lucci, Carlos de Sousa; Rodrigues, Paulo Henrique Mazza; Melotti, Laércio (Brazilian Journal of Veterinary Research and Animal Science, 1999)
Four crossbred Holstein 2 month lactating cows with 470 kg of average live-weight, fitted with rumen canulas, were used in a change over design, in a 2 x 2 factorial arrangement with four treatments: without or with sodium lasalocid (200 mg/cow/day); and two concentrate/roughage ratios: 30%-70% and 60%-40%. Milk and fat production, dry matter consumption, ruminal pH and liquid turnover rates were measured. Lasalocid resulted in higher but not statistically significant increase in milk production with the 70% roughage diet. Rich concentrate diets (60%) resulted in higher, but not statistically significant, dry matter consumption; these diets increased milk, fat corrected milk and milk protein production, and decreased fat milk production, as well as the ruminal pH at 6 hours after the first meal.